ANALISIS PENGELOLAAN LABORATORIUM PRODUKTIF AKUNTANSI (BANK UNIT PRODUKSI) SEBAGAI SARANA PEMBELAJARAN SISWA AKUNTANSI PADA SEKOLAH MENENGAH KEJURUAN NEGERI SE-SURAKARTA - Kumalasinta, Rani; Witurachmi, Sri; Ivada, Elvia (Jupe-Jurnal Pendidikan Ekonomi, 2013)
ABSTRAKTujuan penelitian ini adalah untuk mengetahui: ketersediaan sarana dan prasarana di laboratorium unit produksi menurut Peraturan Menteri Pendidikan Nasional RI No. 40 tahun 2008 tentang Standar Sarana dan Prasarana untuk Sekolah Menengah Kejuruan/ Madrasah Aliyah Kejuruan, pengelolaan laboratorium Unit produksi, pelaksanaan kegiatan praktik di laboratorium unit produksi, kendala-kendala yang dihadapi sekolah dalam mengelola laboratorium unit produksi, dan upaya sekolah dalam mengatasi kendala yang muncul dalam mengelola laboratorium unit produksi.Penelitian ini merupakan penelitian deskriptif kualitatif, objek penelitian adalah seluruh SMK Negeri Se-Surakarta Bidang Bisnis Manajemen. Teknik pengumpulan data yang digunakan adalah wawancara, observasi, angket dan dokumentasi. Teknik pengambilan sempel menggunakan purposive sampling dan snowball sampling. Uji validitas data dalam penelitian ini melalui triangulasi metode dan triangulasi sumber.Hasil penelitian menunjukkan bahwa: tingkat ketersediaan sarana dan prasarana di laboratorium unit produksi sebagai sarana pembelajaran siswa akuntansi pada SMK Negeri Se-Surakarta dikategorikan baik dan tidak menyimpang dari Peraturan Menteri No. 40 tahun 2008, dengan rata-rata tingkat persentase 72,92% dan rata-rata skor 3,64; tingkat pengelolaan laboratorium unit produksi sebagai sarana pembelajaran siswa akuntansi pada SMK Negeri Se-Surakarta mulai dari perencanaan, pengorganisasian, pelaksanaan, serta pengawasan dan evaluasi, dikategorikan baik dengan rata-rata tingkat persentase 80,57% dan rata-rata skor 4,03; pelaksanaan kegiatan praktik di laboratorium unit produksi sebagai sarana pembelajaran siswa akuntansi pada SMK Negeri Se-Surakarta dikategorikan baik dengan rata-rata tingkat persentase 83,53% dan rata-rata skor 4,17; kendala yang muncul yaitu masih terdapat sekolah yang sarana prasarana belum sesuai standar, belum terdapat software, terbatasnya waktu pengelolaan, belum adanya karyawan khusus, kurangnya ketelitian siswa saat praktik; dan upaya yang dilakukan adalah berusaha meningkatkan sarana dan prasarana, menggunakan Microsoft Excel, membuat jadwal piket guru akuntansi untuk memantau siswa saat praktik, pembimbing praktik memberikan masukan kepada siswa agar lebih teliti.Kata kunci: pengelolaan laboratorium, laboratorium akuntansi, pembelajaran praktik akuntansi ABSTRACTThe objectives of this research are to investigate: the availability of facilities and infrastructures at the production unit laboratories pursuant to Regulation of the Ministry of National Education of the Republic of Indonesia Number: 40 of 2008 regarding the Standards of Facilities and Infrastructures for Vocational High Schools/Islamic Vocational High Schools; the management of production unit laboratories; the implementation of practicum activities at the production unit laboratories; the constraints encountered in the implementation of management of production unit laboratories; and the efforts done by the schools of dealing with the existing problems in managing the production unit laboratories.This research used the descriptive qualitative research method. Its objects were all of Management Business Fields, State Vocational High Schools of Surakarta. The data of the research were collected through in-depth interview, observation, questionnaire, and documentation. The samples of the research were taken by using the purposive sampling technique and the snowball sampling technique. They were validated by using the method and source triangulations.The results of the research show that: the level of availability of facilities and infrastructures at the production unit laboratories as a means of learning for the Accounting students of State Vocational High Schools of Surakarta is in the good category and does not deviate from Regulation of the Ministry of the Ministry of National Education of the Republic of Indonesia Number: 40 of 2008 with the average percentage of 72.92% and the average score of 3.64; the level of management of production unit laboratories as a means of learning of the Accounting students of State Vocational High Schools of Surakarta starting from planning, organization, implementation, supervision to evaluation respectively is in the good category with the average percentage of 80.57% and the average score of 4.03; the implementation of practicum activities at the production unit laboratories as a means of learning for the Accounting students of State Vocational High Schools of Surakarta is in the good category with the average percentage of 83.53% and the average score of 4.17; the constraints encountered in the implementation of management of the production unit laboratories are as follows: some schools have facilities and infrastructures which are not incompliant with the required standards, there is not software, the time for management is limited, there is not any specialized staff for managing the production unit laboratories, the students are less careful when doing practicum activities; and the efforts done of dealing such constraints are as follows: striving to improve the facilities and infrastructures, using Microsoft Excel software, making schedules for the Accounting teachers to supervise the students when having practicum activities, and encouraging the practicum guiding teachers to extend inputs to the students so as to act thoroughly when doing practicum activities.Keywords: Laboratory management, Accounting productive laboratory, and Accounting practicum learning